(untitled) (Asian Education Studies, 2022)
Higher education is an important link that deeply affects the improvement of the overall quality of the nation and the development of the national economy. Our party and state attach great importance to higher education, especially the ideological and political education of college students in the new era. The core literacy construction of college counselors in the new era should keep up with the pace of the times. With the rapid development of society and the complex changes in the growth environment of universities, the standards should be continuously improved, strategies should be adjusted, and construction plans should be optimized.